2001
DOI: 10.1136/sti.77.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral drug concentrations in semen of HIV-1 infected men

Abstract: Because semen is a major vehicle for the sexual transmission of HIV-1, control of viral replication within the sanctuary of the male genital tract should be a goal of antiretroviral therapy. Local immune responses, virus specific factors, and the degree of viral and cellular traYcking all appear to be important in controlling viral replication and evolution. However, the most important factor influencing viral replication and evolution within the male genital tract may be the disposition of antiretroviral agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 49 publications
1
53
1
2
Order By: Relevance
“…Although it is not a common practice to collect semen in human ADME studies, detection of drugs and their metabolites in semen has been reported previously, particularly in patients with HIV (Ette et al, 1988; Taylor and Pereira, 2001;Avery et al, 2013). Semen was evaluated since subjects in prior studies had reported semen discoloration after taking KAE609 at higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not a common practice to collect semen in human ADME studies, detection of drugs and their metabolites in semen has been reported previously, particularly in patients with HIV (Ette et al, 1988; Taylor and Pereira, 2001;Avery et al, 2013). Semen was evaluated since subjects in prior studies had reported semen discoloration after taking KAE609 at higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the detection of HIV-1 RNA in the semen of highly active anti-retroviral therapy-treated seropositive men, even in the absence of detectable levels of viral RNA in plasma, indicates that the male reproductive tract may constitute a sanctuary for HIV-1 replication. 4 -9 Indeed, subtherapeutic concentrations of protease inhibitors are evidenced in semen, 10 and sexual transmission of drug-resistant strains are currently on the rise. [11][12][13] Few previous studies have sought the presence of HIV in testes from acquired immune deficiency syndrome (AIDS)-deceased men, and what data there are remain controversial, 1 whereas, for obvious ethical reasons, in-depth investigations of the impact of HIV on the testis of asymptomatic men have never been performed.…”
mentioning
confidence: 99%
“…[8,9]. Außerdem ist zu bedenken, dass nicht alle antiretroviralen Medikamente in den Genitalflüssigkeiten dieselben therapeutisch wirksamen Konzentrationen erreichen wie im Plasma und dass es daher im genitalen Viruskompartiment zu einer Resistenzbildung kommen kann, die sich zunächst in Blutuntersuchungen nicht widerspiegelt [10,11]. Schließlich ist auch noch zu berücksichtigen, dass es bei inkonsequenter Einnahme der Medikamente zu einer phasenhaften Virusreplikation und schließlich ebenfalls zu einer Resistenzentwicklung kommen kann [12].…”
Section: Introductionunclassified